2015
DOI: 10.1007/s00027-015-0394-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water temperature on summer periphyton biomass in shallow lakes: a pan-European mesocosm experiment

Abstract: Periphyton communities play an important role in shallow lakes and are controlled by direct forces such as temperature, light, nutrients, and invertebrate grazing, but also indirectly by planktivorous fish predation. We performed a pan-European lake mesocosm experiment on periphyton colonization covering five countries along a north/south geographical/temperature gradient (Estonia, Germany, Czech Republic, Turkey, and Greece). Periphyton biomass on artificial polypropylene strips exposed at 50 cm water depth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 40 publications
1
20
0
2
Order By: Relevance
“…The absence of (negative) effects may reflect an oversimplification of our predator assemblages, particularly with a lower richness of fish under our experimental than under natural conditions, leading to greater availability of alternative, more nutritious food sources, such as zooplankton and macroinvertebrates. Moreover, the low mean densities of plant-associated macroinvertebrates in our study might be an effect of the short colonization phase and low accessibility to the mesocosms, notably of snails, which may have prevented indirect positive effects of fish on periphyton, as previously reported for temperate systems [17,85,87,88]. Besides, the extremely high PVI used (ca.…”
Section: Discussionmentioning
confidence: 49%
“…The absence of (negative) effects may reflect an oversimplification of our predator assemblages, particularly with a lower richness of fish under our experimental than under natural conditions, leading to greater availability of alternative, more nutritious food sources, such as zooplankton and macroinvertebrates. Moreover, the low mean densities of plant-associated macroinvertebrates in our study might be an effect of the short colonization phase and low accessibility to the mesocosms, notably of snails, which may have prevented indirect positive effects of fish on periphyton, as previously reported for temperate systems [17,85,87,88]. Besides, the extremely high PVI used (ca.…”
Section: Discussionmentioning
confidence: 49%
“…Climate warming is expected to affect the production and composition of both periphytic and planktonic algae through its direct effect on the physical properties of the water column (Smol et al, 2005;Jeppesen et al, 2009Jeppesen et al, , 2011Rühland et al, 2015) and indirectly by their effect on light availability and nutrient levels in lakes (Salmaso, 2005;Winder and Hunter, 2008;Rühland et al, 2015). How periphyton is affected by global warming is, however, debated (Mahdy et al, 2015). Some studies have shown that warming coupled with nutrient addition alters the temperature effects on periphyton, suggesting complex interactive effects of nutrient and temperature (Trochine et al, 2014;Piggott et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The light conditions in lakes influence the growth of the plankton community, and the eutrophication caused by the high concentration of chlorophyll-a would impact light availability in lakes [6,7]. Excessive nitrogen and phosphorus inputs are important factors to shift lakes from oligotrophic to hypertrophic conditions [8], and lead to dramatic increases in harmful cyanobacteria blooms, which would create a serious threat to lake ecosystems [9].…”
Section: Introductionmentioning
confidence: 99%